Pengaruh Gaya Kepemimpinan, Motivasi Kerja, dan Semangat Kerja terhadap Kinerja Karyawan Pabrik Podo Seneng - Halla Binti Abdulah; Indah Listyani; Rike Kusuma Wardhani (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to determine whether there is an effect of leadership style (X1), work motivation (X2), and work enthusiasm (X3) on employee performance (Y) at Podo Seneng Factory. This research uses a quantitative approach with data collection techniques through surveys, utilizing questionnaires as the main instrument for obtaining primary data. Additionally, secondary data were collected from relevant literature studies and documentation. The sampling technique used is saturated sampling, where all members of the population who meet the research criteria are selected as the sample. Data analysis was carried out in several stages, starting with validity and reliability tests to ensure the quality of the research instruments. The next step is the classical assumption test to check whether the data meet the basic assumptions of regression analysis. The analysis technique used in this study is multiple linear regression analysis to determine the effect of independent variables on the dependent variable. The T-test is used to determine the significance of the effect of each independent variable on employee performance, while the F-test is used to examine the simultaneous effect of all independent variables on the dependent variable. Additionally, the coefficient of determination test is used to assess how well the independent variables can explain the variation in the dependent variable. The results of this study are expected to provide a clearer understanding of the factors affecting employee performance at Podo Seneng Factory.